Peculiarities of organization of propaganda of non-Olympiс sports in Kharkiv - Stadnik, Svetlana; Bondar, Taras; Orlenko, Olena; Petrenko, Irina (Slobozhanskyi Herald of Science and Sport, 2019)
This work is actual due to rapid growth of the popularity of non-Olympic sports in the city of Kharkiv. Identification of organizational reserves in non-Olympic propaganda system of sports in the city of Kharkiv and identification of areas of its improvement is aimed at the development of non-Olympic movement in the city. Purpose: definition of features and ways to improve the system of propaganda of non-Olympic sports in the city of Kharkiv. Material & Methods: during the research a set of scientific methods was used: Analysis of literary sources; Analysis of documentary materials; Analysis of Internet resources; System analysis; Organizational analysis; Survey (questionnaire), methods of mathematical statistics. In a study coaches and clients of fitness clubs in Kharkiv and students of Kharkiv sate academy of physical culture who are involved in non-Olympic sports (n=50) participated. Results: a system of propaganda of non-Olympic sports in the city of Kharkiv from the perspective of a systematic approach is characterized. Analyzed local promoter activity of management of the State's authority s in the sphere of physical culture and sport, the Federation and the other sports organizations of non-Olympic sports. The regional mass media have been identified, which cover information on non-Olympic sports. Organizational reserves are revealed. Conclusions: the propaganda system of non-Olympic sports in the city of Kharkiv is characterized by its singularities in use of existing forms and means of propaganda in the existing resource provision and in regional media. Directions of improving the system of propaganda of non-Olympic sports in the city of Kharkiv are offered.